Microsphere enabled subdiffraction-limited optical-resolution photoacoustic microscopy: a simulation study - Upputuri, Paul Kumar (2017)
Optical resolution photoacoustic microscopy (ORPAM) is a high-resolution hybrid imaging modality having potential for microscale in vivo imaging. Optical diffraction limits the lateral resolution of ORPAM. A photonic nanojet (PNJ) was used to break this diffraction limit. A single round microsphere can generate a PNJ with subwavelength waist, but its short axial length limits its applications to surface imaging only. We investigate different sphere designs to achieve ultralong nanojets that will make the nanojet more viable in far-field applications, such as photoacoustic imaging. The PNJ properties, including effective length, waist size, working distance, and peak intensity, can be tuned and controlled by changing the sphere design and its refractive index. A truncated multilayer microsphere design could generate an ultraelongated PNJ with length larger than ∼172λ (∼138  μm) while retaining a large working distance ∼32λ (∼26  μm). Through simulation study, we observed ∼11-fold enhancement in lateral resolution with 5  μm round sphere (refractive index 2.2) when used in a conventional ORPAM setup with NA=0.1 and λ=800  nm.